2021
DOI: 10.1111/gcb.15550
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale importance of microbial carbon use efficiency and necromass to soil organic carbon

Abstract: Optimal methods for incorporating soil microbial mechanisms of carbon (C) cycling into Earth system models (ESMs) are still under debate. Specifically, whether soil microbial physiology parameters and residual materials are important to soil organic C (SOC) content is still unclear. Here, we explored the effects of biotic and abiotic factors on SOC content based on a survey of soils from 16 locations along a ~4000 km forest transect in eastern China, spanning a wide range of climate, soil conditions, and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(109 citation statements)
references
References 42 publications
7
70
0
Order By: Relevance
“…Finally, the N content of all samples was measured using an elemental analyzer (Vario MAX CN Elemental Analyzer, Elementar, Germany). pH of the soils was determined using a pH meter (Ultrameter II, United States) ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the N content of all samples was measured using an elemental analyzer (Vario MAX CN Elemental Analyzer, Elementar, Germany). pH of the soils was determined using a pH meter (Ultrameter II, United States) ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The soil microbial community is an important biotic component of soil and an important driving force of many soil ecological processes ( Wang et al, 2021 ). Due to the high sensitivity of soil microbes, the increase in N deposition is bound to have a significant impact on the soil microbial community; however, the response to N deposition often differs in different ecosystems, and the relationship between the soil microbial community and soil factors is uncertain ( Xiao et al, 2020 ; He et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the predominant contribution of microbial necromass C to stable soil C pool, increasing attention has been paid to determinants of soil microbial necromass C. It has been reported that microbial necromass C is regulated by climatic conditions (Ma et al, 2018; Ni, Liao, Tan, Peng, et al, 2020), soil physicochemical properties (Chen et al, 2020; Ni, Liao, Tan, Wang, et al, 2020), as well as microbial properties (Wang et al, 2021). Despite progressive exploration made thus far, our knowledge on this issue remains inadequate since current investigations have primarily focused on the topsoil above 30 cm (e.g., Ma et al, 2018; Liang et al, 2019; Chen et al, 2020), with relatively limited evidence from subsoil.…”
Section: Introductionmentioning
confidence: 99%